Physiotherapy for patients on extracorporeal membrane oxygenation support: How, When, and Who. An international EuroELSO survey - Massimiliano Polastri; Allaina Eden; Antonio Loforte; Andrea Dell’Amore; Marta Velia Antonini; Jordi Riera; Nicholas A Barrett; Justyna Swol (SAGE Journals, 2022)
Background and purpose
Extracorporeal membrane oxygenation (ECMO) continues to play an essential role in organ support in cardiogenic shock or acute respiratory distress syndrome and bridging to transplantation. The main purpose of the present survey was to define which clinical and organizational practices are adopted for the administration of physiotherapy in adult patients undergoing ECMO support worldwide.
Methods
This international survey was conceived in November 2021. The survey launch was announced at the 10th EuroELSO (European ELSO chapter) Congress, London, May 2022.
Results
The survey returned 32 questionnaires from 29 centers across 14 countries. 17 centers (53.1%) had more than 30 intensive care unit beds available and most (46.8%) were able to care for five to 10 patients on extracorporeal life support simultaneously. The predominant physiotherapist-to-patient ratio was 1:>5 (37.5%); physiotherapy was available 5/7 days and 7/7 days by 31.2% and 25% respectively. Respiratory physiotherapy was not defined by a specific protocol in most centers (46.8%) while 31.2% declared that the treatment commences less than 12 h after sedation is stopped/reduced. Mostly, early physiotherapy in non-cooperative ventilated patients was provided within the first 48 h (68.6%) and consisted of as passive range of motion, in-bed positioning, and splinting. Postural passages and sitting were provided to patients and walking was included in those advanced motor activities which are part of the treatment.
Conclusion
Physiotherapy in patients on ECLS is feasible, however substantial variability exists between centers with a trend of delivering not protocolized and understaffed rehabilitation practices.
Keywords: Cardiology; 110323 Surgery